Genome-Wide Analysis Uncovers Novel Recurrent Alterations in Primary Central Nervous System Lymphomas - Braggio, Esteban; Van Wier, Scott; Ojha, Juhi; McPhail, Ellen; Asmann, Yan W.; Egan, Jan; da Silva, Jackline Ayres; Schiff, David; Lopes, M. Beatriz; Decker, Paul A.; Valdez, Riccardo; Tibes, Raoul; et al. (Clinical cancer research, 2015)
Purpose: Primary central nervous system lymphoma (PCNSL) is an aggressive non-Hodgkin lymphoma confined to the central nervous system. Whether there is a PCNSL-specific genomic signature and, if so, how it differs from systemic diffuse large B-cell lymphoma (DLBCL) is uncertain. Experimental Design: We performed a comprehensive genomic study of tumor samples from 19 immunocompetent PCNSL patients. Testing comprised array-comparative genomic hybridization and whole exome sequencing. Results: Biallelic inactivation of TOX and PRKCD was recurrently found in PCNSL but not in systemic DLBCL, suggesting a specific role in PCNSL pathogenesis. In addition, we found a high prevalence of MYD88 mutations (79%) and CDKN2A biallelic loss (60%). Several genes recurrently affected in PCNSL were common with systemic DLBCL, including loss of TNFAIP3, PRDM1, GNA13, TMEM30A, TBL1XR1, B2M, CD58, activating mutations of CD79B, CARD11, and translocations IgH-BCL6. Overall, B-cell receptor/Toll-like receptor/NF-κB pathways were altered in >90% of PNCSL, highlighting its value for targeted therapeutic approaches. Furthermore, integrated analysis showed enrichment of pathways associated with immune response, proliferation, apoptosis, and lymphocyte differentiation. Conclusions: In summary, genome-wide analysis uncovered novel recurrent alterations, including TOX and PRKCD, helping to differentiate PCNSL from systemic DLBCL and related lymphomas. Clin Cancer Res; 21(17); 3986–94. ©2015 AACR.